The Early Christian Period and the Latin Middle Ages - Strunk, Oliver 1901-1980; McKinnon, James (New York Norton, 1998)
In The Early Christian Period and the Latin Middle Ages, we witness the merger of musica, then an abstract academic enterprise, and cantus, or practical music. The volume spans a millennium of writings, ranging from scriptural commentaries by St. Jerome and other fourth-century Church Fathers to an excerpt from Speculum musicae, an extensive fourteenth-century treatise by Jacques of Liège. Along the way we read from the works of St. Augustine, Boethius, Hildegard of Bingen, Guido of Arezzo, Franco of Cologne, and a score of others, all in impeccable English translations prepared or revised by James McKinnon.
Keywords: Classical Antiquity (8th Century BC-6th Century AD); Middle Ages (500-1400); Music history